Improving Islamic Religious Education Learning through Sort and Paste Worksheets and Think-Pair-Share Strategy - Devi Rofidah Celine; Irma Soraya; Mohammad Kurjum (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2025)
The learning process of Islamic Religious Education (PAI) at the Madrasah Ibtidaiyah level is often faced with the challenge of low student engagement and the lack of learning media that is in accordance with the developmental characteristics of early grade students in Madrasah Ibtidaiyah. Many students have difficulty understanding abstract material because the learning approach is less interactive and monotonous. This study aims to explore the optimization of Islamic Religious Education (PAI) learning through the use of Sort and Paste Worksheet developed with the Dick and Carey learning design model and activated in a cooperative learning strategy of Think-Pair-Share type. This collaboration between media and methods is designed to improve the competence of grade 2 students at MI Sayyid Abdurrahman I. This study used a descriptive qualitative approach with a field research method to investigate the implementation of the media in the learning process. Data were collected through in-depth interviews with PAI teachers, direct observation of learning activities in the classroom, as well as analysis of documents and student work. The results showed that the use of Sort and Paste Worksheet significantly improved students' learning experience through increased active engagement, retention of material understanding, and development of fine motor skills. In addition, this method also aroused students' enthusiasm for PAI subjects, making them more interesting and contextualized. Thus, this study concludes that integrating Sort and Paste Worksheet into cooperative learning strategies greatly facilitates the implementation of the scientific approach through the stages of observing, questioning, trying, reasoning, and is effective for optimizing PAI learning, especially in building a strong religious foundation for early grade students in Madrasah Ibtidaiyah.